Ccdc61 controls centrosomal localization of Cep170 and is required for spindle assembly and symmetry - Bärenz, Felix; Meyer, Annalena; Lorenz, Holger; Hoffmann, Ingrid (Molecular biology of the cell, 2018)
Microtubule nucleation was uncovered as a key principle of spindle assembly. However, the mechanistic details about microtubule nucleation and the organization of spindle formation and symmetry are currently being revealed. Here we describe the function of coiled-coil domain containing 61 (Ccdc61), a so far uncharacterized centrosomal protein, in spindle assembly and symmetry. Our data describe that Ccdc61 is required for spindle assembly and precise chromosome alignments in mitosis. Microtubule tip-tracking experiments in the absence of Ccdc61 reveal a clear loss of the intrinsic symmetry of microtubule tracks within the spindle. Furthermore, we show that Ccdc61 controls the centrosomal localization of centrosomal protein of 170 kDa (Cep170), a protein that was shown previously to localize to centrosomes as well as spindle microtubules and promotes microtubule organization and microtubule assembly. Interestingly, selective disruption of Ccdc61 impairs the binding between Cep170 and TANK binding kinase 1, an interaction that is required for microtubule stability. In summary, we have discovered Ccdc61 as a centrosomal protein with an important function in mitotic microtubule organization.
Gesehen am 03.03.2020